Sunny walking counts more - Zhang Rui; Chen Hong; Liu Yi-xiao; Zhang Wen-hui; Lu Qin; Yamanishi Hiromichi; Yamanishi Chiaki; Yamanishi Kyosuke; Qiu Yu-lan; Ye Xiao-fei; Huang Zi-rui; Zhang Bo-yuan; et al. (Acta Pharmacologica Sinica, 2019)
In our previous article entitled “Low-intensity walking as mild medication for pressure control in prehypertensive and hyperten-sive subjects: how far shall we wander?” published in this journal [1], we reported mild but signiﬁcant reductions in both blood pressure (BP) and heart rate (HR) after low-intensity walking at a speed of 3 km/h (2.5 metabolic equivalents of task, METs), accompanied by a transient elevation in urine β-endorphin. In a recent study observing environmental inﬂuence on low-intensity walking, we found unexpectedly interesting results that we would like to share with the readers of the journal.